Research on Religion in Croatian Ethnology - Šantek, Goran-Pavel (Array, 2004)
This paper is intended to offer the interested reader an insight into the Croatian specificity in ethnological research of religion. Despite the non-institutionalisation of the subject, Croatian ethnologists have touched on religious themes, either at an ethnographic, or at an ethnological or anthropological level.